Si vis pacem, para bellum. "El Príncipe", la Fortuna y la guerra - Tizziani, Manuel (Ingenium. Revista Internacional de Pensamiento Moderno y Metodología en Historia de las Ideas, 2014)
Is war a way to peace? This question, which in the eyes of Hannah Arendt will be no more than a falsehood of the militaristic crusade, will prove to be a topic almost unavoidable for anyone to undertake the task of thinking philosophically about violence, its origins and implications. Niccolò Machiavelli, imbued with a universe of wars, intrigue, and political ups and downs, will not be an exception to this rule. It is to him whom we dedicate this study: based on The Prince, in the first section we analyze the centrality of the concepts of virtú, Fortune and occasion. Later, we rehearse a reflection on the observations Machiavelli performs around the issue of war. Our ultimate objective is none other than trying to unravel and understand what should be, in the version of the Florentine, the relationship between a virtuous prince and armies.
Keywords: Fortune; virtú; occasion; war; violence; laws